In Vitro Evaluation of Antimicrobial Activity of Psidium guajava Leaf Extract against Selected Pathogenic Bacteria (Journal of Pharmaceutical Negative Results, 2022)
Guava production in India, which accounts for 25 million metric tonnes or 45% of global production, is the highest. China (7%) and Indonesia (5%) are the second and third largest producers. Guava is a rich source of vitamin C which is most effective to cure UTI diseases. Leaf extracts in different solvents (Water, Benzene and methanol) prepared by Soxhlet extraction method were tested against two gram positive and two gram negative bacteria (Isolated from patient infected with UTI) by agar well diffusion method. Results indicated that methanol extract was most effective against Staphylococcus aureus, followed by Enterococcus faecalis (Gram positive)(17mm) in methanol extracts. In benzene extracts zone of inhibition were of 17 mm against Staphylococcus aureus (Gram positive), Enterococcus faecalis Gram positive) and similar pattern was in water extracts. In case of gram negative bacteria zone of inhibition was 13mm against Pseudomonas aeruginosa (Gram negative) in methanol extract and similar pattern was observed in benzene and water extracts. Gram positive bacteria were more sensitive than gram negative bacteria. This antimicrobial property in guava leaf is due to phenolic compounds present in it.